OPINIONS OF THE STUDENTS OF THE FACULTY OF EDUCATION ON THEIR UNDERGRADUATE TEACHER PREPARATION - CHRASKOVA, Marie; CHRASKA, Miroslav (Trends in education, 2013)
The paper describes the results of research. By means of a questionnaire we surveyed the opinions of the students on their undergraduate teacher preparation. It was found out that the students are in most cases satisfied with the quality of their undergraduate teaching preparation. Nevertheless, the students require the extension of teaching practice in schools as well as involving more possibilities for practising model situations in the classroom. One of the interesting findings of the research is the fact that the fulfilment of student expectations is associated with the type of a study course taken at the Faculty of Education. It was revealed that both the specialization (natural sciences, social sciences, special-pedagogy) and a type of completed secondary school are significantly important factors. On the other hand, the survey showed that gender of students has no impact on fulfilment of expectations associated with the study at the Faculty of Education
Keywords: student; Faculty of Education; undergraduate teacher preparation; questionnaire